PROTECTION OF THE ADULT THROUGH JUDICIAL COUNSELLING AND SPECIAL GUARDIANSHIP. GENERAL CONSIDERATIONS AND ASPECTS OF COMPARATIVE LAW - Larisa-Diana ONEA (Challenges of the Knowledge Society)
This paper aims to analyse the implications of „Law no. 140/2022 on some protection measures for people with intellectual and psychosocial disabilities and the amendment and completion of some legal acts” in Romania, by reviewing the aspects pointed out by the CCR in its unconstitutionality dec. no. 601/2020. This paper will also analyse legislative regulations on the protection of the adult in different legal systems.